Effectiveness of HIV/AIDS educational intervention in increasing knowledge, attitude and practices for primary school teachers in some part of Africa - Mustapha, Abdu; Umar, Ahmad; Ibrahim, Faisal; Syed Hassan, Syed Tajuddin; Ismail, Suria; Yakasai, Musa Garba (Elsevier, 2016)
Human immunodeficiency virus (HIV) is virus that weakens the immune system of the body through destruction of the white blood cells. Whereas, AIDS term as; acquired immune deficiency syndrome is a disease due to the infection of HIV. Knowledge of health, and practices among teachers of primary school are scanty. Studies indicated that few teachers have heard or even became aware that HIV/AIDS is a viral infectious, and some of them lacked the knowledge about its mode of transmission with low attitudinal behaviours. Thus, this review paper discusses some health promotion measures and relevant information regarding, how the use of educational intervention in primary school teachers, could help in reducing the incidence cases of HIV/AIDS in Africa. We therefore recommend effective educational intervention programmes should be set for primary school teachers, in order that the teachers and the students could have a sound knowledge of health practices that will change their attitude which in turn reduce the risk of HIV/AIDS transmission.